Spatial justice in participatory planning: an integrated framework and lessons from practice - Gonçalves, Juliana E.; Rocco, Roberto; Sitzoglou, Maria; Michail, Nafsika; Kupper, Diana; Grafakos, Stelios; Djuraskovic, Milutin; Veeckman, Carina; Pantelidis, Nick; Gkatsikos, Alexandros; Vrochidis, Stefanos; Dieguez-Seoane, Alberto; et al. (Frontiers in Sustainable Cities, 2025)
Climate change is driving cities to transition toward more sustainable urban systems, often implementing these transitions through spatial interventions. However, without a deliberate focus on spatial justice, such climate initiatives risk exacerbating existing socio-spatial inequalities, leading to issues such as green gentrification and maladaptation, which affect vulnerable populations the most. Participatory practices have the potential to foster just transitions, yet they are not well integrated into planning and design processes and are insufficiently linked to spatial justice. This paper introduces a framework that integrates participatory approaches into a typical planning and design cycle through a spatial justice perspective. The framework is applied to eight cases in various geographical contexts, encompassing a range of practices from participatory planning workshops to the development of digital participation tools. Our findings suggest that the framework enables both researchers and practitioners to adopt a more holistic approach to participation in planning and design. Furthermore, we identify key enablers, barriers, and lessons learned from these cases, offering insights that can inform urban practitioners, policymakers, and researchers in advancing spatial justice through participatory planning. Ultimately, this study contributes to enabling just urban transitions by providing a structured approach to embedding spatial justice in participatory planning and design.